ANALYSIS OF MODERN PROBLEMS AND PROSPECTS FOR CROSS-BOUNDARY COOPERATION OF THE RF AND RK IN THE FIELD OF ENVIRONMENTAL MANAGEMENT AND ENVIRONMENTAL SAFETY ON THE EXAMPLE OF THE TRANS VOLGA-URAL STEPPE REGION - Тургумбаев, Акан (Вестник ЗКУ, 2024)
The objective prerequisites and grounds for the development of transboundary Kazakh-Russian cooperation on the conservation and restoration of steppes in the post-Virgin Land area within the Trans-Volga-Ural region are considered. The areas in which the development of cooperation is fundamental for the future fate of the naturally unified post-virgin space are noted. Examples of the implementation of projects supported by global international funds show the main achievements on the Russian and Kazakh sides. Current problems and prospects for cooperation are noted.